Fables. [17], Inherit the wind - Willingham, Bill (Fables, 2012)
"The fearsome Mister Dark is dead, killed in a kamikaze attack by the only entity colder than himself: the North Wind, King of the Frozen Wastes, Ruler of the Cardinal Winds - and Bigby Wolf's deadbeat dad."--P. [4] of cover.